Erythrocyte Morphology of Tuberculosis Patients - Ahmad Rifa'i; Ahmad Muhlisin (Tropical Health and Medical Research, 2019)
Tuberculosis is one of the causes of anemia in chronic diseases in addition to rheumatoid arthritis, urserative colitis, Crohn's disease, ovarian malignancy and Hodgkin's lymphoma. Chronic disease anemia also known as anemia due to inflammation, occurs in patients with chronic infections. This anemia also occurs in some patients with malignancy. The causes of anemia are based on cell size, namely iron deficiency (often), anemia of chronic diseases (often), Thalassemia (often in certain ethnicities) causing the size of cells to become microsytic. Cells turn macrocytic due to liver disease, excess alcohol, megaloblastic anemia (vitamin B12 deficiency or folate or exposure to certain drugs), hemolysis, and aplastic anemia. Whereas the normal cell factors are blood loss, the initial phase of iron deficiency, anemia, chronic disease, and kidney failure. The aim of this study was to determine the type of anemia based on the morphological description of erythrocytes in the form, color, and size of erythrocytes seen in the smear blood supply of tuberculosis patients based on treatment duration of 0-6 months. The type of research used was a descriptive survey with a population of 15 people taken by accidental sampling. Data collection is done by examining the blood smear smears. Based on the examination of peripheral blood smear preparations in pulmonary tuberculosis patients, the morphology of erythrocytes in the form of Normocytic normochrome was 74% and microsocytic normochrome was 26%. Suggestions in the research for further research can be carried out with support other than the examination of peripheral blood smear.